Pengembangan Bahan Ajar Interaktif Berbasis Etnokimia Budaya Dayak (Kalimantan Tengah) Pada Materi Termokimia - Alfalita Chendy Sarungu; Suandi Sidauruk; Abudarin Abudarin (Jurnal Ilmiah Kanderang Tingang, 2026)
This study aims to explore and develop local culture into teaching materials. The production of Baram and betel lime can be used as examples to study thermochemical concepts, thereby producing interactive teaching materials based on Dayak (Central Kalimantan) ethnochemistry in thermochemistry. This research is a Research and Development (R&D) study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This research was conducted at SMA Negeri 1 Palangka Raya with 80 grade XI phase F students as research subjects. Data were collected through validity questionnaires, pretest and posttest questions, and teachers response questionnaires. Interactive teaching materials based on Dayak (Central Kalimantan) ethnochemistry in thermochemistry can enrich the study of local culture utilization, especially in chemistry learning in thermochemistry, and become an alternative teaching material and learning resource variation during the chemistry learning process. The percentage of teaching material trial results, the percentage of feasibility from subject matter experts was 83.33% and pedagogical experts was 96.88%, readability test was 81.7%, effectiveness with an N-gain value of 0.76 and a Mann-Whitney test sig value of 0.01, and positive responses from chemistry teachers was 88.6%. The trial results show that interactive teaching materials based on Dayak (Central Kalimantan) ethnochemistry on thermochemistry are feasible, easy to understand, and effective to improve student learning outcomes.